Silencing Nogo-B receptor inhibits penile corpus cavernosum vascular smooth muscle cell apoptosis of rats with diabetic erectile dysfunction by down-regulating ICAM-1. - Yun Zhang; Wei Huo; Yan Wen; Hai Li (PLoS ONE, 2019)
Erectile dysfunction (ED) is a major sexual problem for men. Nogo-B receptor (NgBR) has been found to be involved in the regulation of vascular remodeling and angiogenesis. The present study explores the effects of NgBR in penile corpus cavernosum in rats with diabetic ED. Firstly, the ED model of Sprague Dawley rats was established. Hematoxylin-eosin staining and Masson staining were conducted to observe pathological morphology. Immunochemical assay was adopted to detect α-smooth muscle actin (α-SMA), NgBR and intercellular cell adhesion molecule-1 (ICAM-1) expression. Reverse transcription quantitative polymerase chain reaction assay and Western blot analysis were carried out for the assessment of NgBR, factors correlated to ICAM-1, including steroid receptor coactivator (SRC) and proline-rich tyrosine kinase2 (PYK2), and factors associated with apoptosis, including B-cell lymphoma-2 (Bcl-2), Bcl-2 associated protein X (Bax), caspase 3 and cleaved-caspase 3. The results found that capillaries and vascular smooth muscle cell content reduced, and NgBR and ICAM-1 were elevated in rats with diabetic ED. si-NgBR relieved ED by decreasing penile corpus cavernosum smooth muscle systolic percentage and increasing erectile time and rate, intracavernous pressure (ICP)/mean arterial pressure (MAP) and diastolic percentage, improving the pathological changes and inhibiting cavernosum cell apoptosis. si-NgBR also resulted in the down-regulation of ICAM-1 and downstream SRC and PYK2 and promoted α-SMA expression. In conclusion, si-NgBR can provide a potential therapy for diabetic ED in rats by down-regulating ICAM-1, SRC and PYK2, making it a potential therapeutic option for diabetic ED.